2018
DOI: 10.1111/chd.12602
|View full text |Cite
|
Sign up to set email alerts
|

Differences in midterm outcomes in infants with hypoplastic left heart syndrome diagnosed with necrotizing enterocolitis: NPCQIC database analysis

Abstract: Despite similar baseline characteristics, HLHS-NEC infants had significant differences in hospital course compared with HLHS-nNEC neonates. In addition, HLHS-NEC infants were less likely to be fed orally during the entire interstage period. Future studies are needed minimize NEC in this high risk population to possibly improve oral feeds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Cardiac NEC appears to be closely associated with several cardiac pathologies. Single ventricle defects, especially HLHS [ 7 , 10 , 13 , 68 ], account for the majority of CHDs associated with cardiac NEC. The mortality of single ventricle-associated cardiac NEC, approaching 25% with HLHS [ 13 ], is often a result of interplay with and among concomitant risk factors, such as prematurity and LBW.…”
Section: Risk Factors Contributing To Cardiac Nec Pathogenesismentioning
confidence: 99%
“…Cardiac NEC appears to be closely associated with several cardiac pathologies. Single ventricle defects, especially HLHS [ 7 , 10 , 13 , 68 ], account for the majority of CHDs associated with cardiac NEC. The mortality of single ventricle-associated cardiac NEC, approaching 25% with HLHS [ 13 ], is often a result of interplay with and among concomitant risk factors, such as prematurity and LBW.…”
Section: Risk Factors Contributing To Cardiac Nec Pathogenesismentioning
confidence: 99%
“…Necrotizing enterocolitis is more common in neonates with CHD compared to healthy neonates and can be associated with significant morbidity. In an analysis of data from the NPCQIC, the incidence of NEC was 5.8% in 1163 neonates with HLHS with a higher incidence below gestational age of 37 weeks, those requiring extracorporeal membrane oxygenation and those with moderate to severe atrioventricular valve regurgitation at the time of discharge [20]. Infants with NEC had a longer length of stay, lower WAZ and were more likely to be exclusively tube fed at the time of discharge and at the time of SCPC.…”
Section: Factors Contributing To Feeding Challenges and Etiology Of G...mentioning
confidence: 99%
“… 47 Lopez et al found that the incidence of extracorporeal membrane use was higher and HLHS patients who developed NEC were more likely to have moderate to severe atrioventricular valve regurgitation at times of discharge from the NPC-QIC database analysis. 45 In another study, Weiss et al 48 noted the rates of intra-abdominal complications to be more frequent in infants who underwent the hybrid procedure than those with the Sano or m-BTS procedure.…”
Section: Cardiac Surgery Perioperative Risk Factors and Necmentioning
confidence: 99%
“…Other than critical cardiac lesions, NEC can also result due to other associations of CHD like prostaglandin therapy, inotrope use, 14 cardiopulmonary bypass (CPB), extracorporeal membrane use, 45 red cell transfusions, especially if multiple. 19 The postoperative period is particularly vulnerable for gut necrosis resulting in significant morbidity and mortality.…”
Section: Cardiac Surgery Perioperative Risk Factors and Necmentioning
confidence: 99%